A Comparative Analysis of Abhavitha and Bhavitha Choorna of Dried Whole Plant of Mandukaparni- Centella Asiatica (Linn.) Urban. Through High Performance Thin Layer Chromatography (AYUSHDHARA, 2023)
HPTLC (High Performance Thin Layer Chromatography) is a powerful analytical technique in the process of drug discovery and evaluation. Due to its dependability and simplicity, it is used as a tool for the identification, authentication, and quality control of herbal drugs. Mandukaparni- Centella asiatica (Linn.) Urban. is a significant and well-known drug expound discussed in the Ayurvedic classics. It is a prostrate, stoloniferous herb with enriched therapeutic potential. The herb is rich in terpinoids, flavonoids, iso-flavonoids, alkanes tannins, saponins, aminoacids and phenylpropanoids, which accounts for its multiple beneficial action in the therapeutics. It has strong anti-inflammatory and antioxidant properties. The Abhavitha choorna (dried powder) and Bhavitha choorna (powder soaked in Mandukaparni swarasa) of dried whole plant of Mandukaparni- Centella asiatica (Linn.) Urban. was subjected to High performance thin layer chromatography and comparative analysis of different peaks in both the Choornas were obtained. The results suggest that change in concentration of phytochemical constituents occur on Abhavitha choorna (powder) to Bhavitha (soaked in Mandukaparni swarasa).